IMPLEMENTASI GERAKAN LITERASI SEKOLAH (GLS) DI LINGKUNGAN SMA PEWARIS PERADABAN PLUS - Setiawati Setiawati; Ichwani Siti Utami; Abi Robian (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2023)
Abstract The School Literacy Movement (GLS) is a massive and structured movement to foster the habits and abilities of students to be able to access, understand, and use something intelligently through various activities, including reading, seeing, listening, writing, speaking and being able to utilize and implement what they know in everyday life. The School Literacy Movement (GLS) is considered effective if students master six basic literacy, namely (1) language literacy, (2) numeracy literacy, (3) scientific literacy, (4) digital literacy, (5) financial literacy, and (6) cultural and civic literacy. The title of the study is "Implementation of the School Literacy Movement (GLS) in the High School Environment of the Heir of Civilization Plus Ciseeng, Ciseeng District, Bogor Regency". This study aims to determine how effective the implementation of the School Literacy Movement Program at SMA Pewaris Civilization Plus Ciseeng; and what positive and negative aspects are contained in the School Literacy Movement Program at SMA Pewaris Civilization Plus Ciseeng. This research is an empirical normative research with a qualitative descriptive analysis approach. The results of the study showed that the implementation of the school literacy movement (GLS) in the Pewaris High School plus Ciseeng Civilization environment was almost entirely going well, although there were still some derivative programs that were not optimal, namely related to financial literacy..